Effectiveness of a parent-mediated intervention for toddlers with autism spectrum disorder: Evidence from a large community implementation. (October 2022) - Brian, Jessica; Drmic, Irene; Roncadin, Caroline; Dowds, Erin; Shaver, Chantelle; Smith, Isabel M; Zwaigenbaum, Lonnie; Sacrey, Lori-Ann R; Bryson, Susan E
Recent efforts have focused on developing and evaluating early intervention for toddlers with probable or emerging autism spectrum disorder. Parent-mediated approaches have gained traction, with mounting evidence of efficacy, but a research-to-practice gap exists, and community effectiveness remains to be firmly established. We report outcomes of a parent-mediated toddler intervention delivered through a research-community partnership, using a community-partnered participatory framework. Data were available for 179 of 183 toddler-parent dyads receiving Social ABCs parent coaching (mean toddler age: 25.18 months; range, 14–34 months). Of these, 89.4% completed the 12-week program and 70.6% returned for 3-month follow-up assessment. Parents attained implementation fidelity exceeding 75%, and toddlers made gains on proximal and distal measures of social communication. Parent fidelity was associated with toddlers' responsivity at week 12, and responsivity predicted later language gains and reduced autism spectrum disorder symptoms. The roles of child, family, and system factors are discussed. Community delivery of an evidence-based parent-mediated intervention for toddlers with autism spectrum disorder is feasible and effective. Given resource efficiencies associated with parent-mediated approaches, findings bolster current efforts to promote earlier and more widespread access to intervention at the first signs of developmental concern. Lay abstract: In an effort to increase access to intervention as early as possible for toddlers with autism spectrum disorder or signs thereof, many researchers have developed interventions that can be delivered by parents in their own homes. These parent-mediated approaches have gained a lot of research attention in recent years and have been found to be helpful in terms of parent and toddler learning. Several studies have used a rigorous research design (a randomized controlled trial) to show that parent-mediated intervention can work under ideal well-controlled conditions. To build on this evidence, we also need to examine whether parent-mediated interventions can be taught well through community service providers and delivered in more "real-world" conditions. This study used a research-community partnership to provide a parent-mediated intervention (called the Social ABCs) to 179 families (mean toddler age was 25 months; ranging from 14 to 34 months). Almost 90% of the families completed the 12-week program and 70% returned for a follow-up assessment 3 months later. Analyses showed that parents learned the strategies that were designed to help them support their toddlers' development. Also, toddlers made gains in their language, communication, and social skills. Importantly, parents' use of the strategies was related to toddlers' skill gains, suggesting that the use of the strategies made a difference for the toddlers. Findings support the use of parent-mediated intervention in this very young age group and suggest that such intervention approaches should be made available for community delivery.